2006
DOI: 10.1300/j005v31n01_10
|View full text |Cite
|
Sign up to set email alerts
|

Chapter 10

Abstract: The current study found that African American residents of Oxford House (OH) used Narcotics Anonymous (NA) at high rates, and that both OH and NA strongly contributed to abstinent social networks. Having siblings and other family members in one's network predicted substance use among network members, whereas spouses, parents, and children did not have an effect on the rate of substance use. These findings suggest that OH and NA may be effective sources of abstinent social support for African Americans recoveri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…Our findings are similar to previous NSAL findings on general service use for mental health disorders that found that African Americans were more likely to use informal help compared to Caribbean Blacks [22]. Other studies have found that Black substance users utilize self-help groups at higher rates, while additional reports indicate there is little difference in the frequency of utilization compared to other racial/ethnic groups, including non-Hispanic Whites [31-34]. Kaskutas and colleagues indicate that self-help groups might be more attractive to Black substance users because they are free and do not require insurance [32].…”
Section: Discussionsupporting
confidence: 89%
“…Our findings are similar to previous NSAL findings on general service use for mental health disorders that found that African Americans were more likely to use informal help compared to Caribbean Blacks [22]. Other studies have found that Black substance users utilize self-help groups at higher rates, while additional reports indicate there is little difference in the frequency of utilization compared to other racial/ethnic groups, including non-Hispanic Whites [31-34]. Kaskutas and colleagues indicate that self-help groups might be more attractive to Black substance users because they are free and do not require insurance [32].…”
Section: Discussionsupporting
confidence: 89%
“…African Americans are well-represented in Oxford Houses in various regions of the U.S. and their outcomes appear to be similar to those of Caucasians (Bishop et al, 1998; Flynn, et al, 2006). However, other ethnic groups such as Hispanics/Latinos, Asian Americans/Pacific Islanders, and AIs are not as well-represented in this program (Alvarez, Jason, Davis, Ferrari, & Olson, 2004; Jason, Davis, et al, 2007).…”
mentioning
confidence: 95%
“…Oxford House residents rated “fellowship with similar peers” the most important aspect of living in an Oxford House (Jason, Ferrari, Dvorchak, Groessl, & Malloy, 1997). The Oxford House experience also provides residents with abstinent-specific social support networks consisting of other residents in recovery (Flynn, Alvarez, Jason, Olson, Ferrari, & Davis, 2006). Individuals who spent more time in an Oxford House had a greater sense of community with others in recovery, less support for substance use (Davis & Jason, 2005), and more support for abstinence (Majer, Jason, Ferrari, Venable, & Olson, 2002).…”
Section: Group Home Sizementioning
confidence: 99%